Analisis Bibliometrik Niat Karyawan Tetap Tinggal - Lusiana, Wiwit; Mujanah, Siti; Fianto, Achmad Yanu Alif (MES Bogor, 2024)
Several scientific publications on employee intentionto stay at work have been carried out, employee intention to stay at work in their organization is a phenomenon that needs attention from an organization. organization is a phenomenon that needs attention from an organization so that employees have a high commitment to their performance and organization so that employees have a high commitment to their performance and the organization. organization. The purpose of this article is to present information about trends in research that has been published on the topic of employee intention to stay at work in 2019-2023. work in the 2019-2023 period. Using a two-stage research method by identifying total journals through Harzing's Publish or Perish software, then conducting bibliometric analysis with VOSviewer. Harzing software, then conducting bibliometric analysis with VOSviewer. Findings The findings showed that there were 200 publications with 21743 citations and 4348.60 citations/year that discuss employee intention to stay at work.Five main clusters were obtained from the bibliometric analysis. In addition, this article this article presents information on research topics that are still little done so that it can be useful for stakeholders. so that it can be useful for stakeholders who need it in future research